الطبيب محمد علي البار وإسهاماته في دمج العلوم التجريبية بالعلوم الشرعية: مدخل تحليلي (The Doctor Medicine Mohamed Ali Al Bar and his Contributions in Integrating the experimental sciences and Islamic Studies: An Analytical Approach) - الدغيشية سعاد بنت سعيد; علي عاصم شحادة (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
تتناول هذه الدراسة حياة الطبيب محمد علي البار وإسهاماته في دمج العلوم التجريبية بالعلوم الشرعية؛ إذ إننا نرى عن طريق تحليل أعماله الكتابية ومشروعاته العلمية، سعيه الحثيث إلى ربط العلوم التجريبية الطبية في مسائل متنوعة بالعلوم الشرعية والنظرة الإسلامية للكون والحياة، فهو نموذج يقتدى به في شخصية الطبيب المسلم الذي لا يفصل العلوم الطبية الحديثة عن العلوم الشرعية، والذي يجعل ارتباطه الديني والروحي نصب عينه في ممارساته الطبية والعلمية، فأعاد إلينا شخصية الأطباء المسلمين الأوائل الذين يعدون فلاسفة وأطباء وأدباء وفقهاء في الوقت نفسه، واتضح ذلك في أمثلة كثيرة من أعماله؛ كبيانه الحكمة من تحريم الخنزير والخمر والمخدرات وكتبه في الصحة العامة، وكتابته في الإعجاز العلمي في القرآن والسنة، وفي استفادته من نظرية التطور والعلوم الحديثة في إثبات قدرة الله، ونقده للمناهج الحالية ودعوته الصريحة إلى إصلاح المناهج الدراسية في كليات الطب وغيرها من الكليات. وتعد موسوعة أخلاقيات مهنة الطب (القضايا الأخلاقية والفقهية في المهن الصحية)، والتي قام بتأليفها مع مجموعة من الأطباء، من أهم إسهاماته في دمج العلوم وتكاملها؛ إذ تعد الموسوعة مرجعا لطلبة الطب وأساتذتهم وجميع العاملين في المهن الطبية وكذلك طلبة العلوم الشرعية وغيرهم. الكلمات المفتاحيّة: محمد البار، دمج العلوم، نقد، المناهج، موسوعة أخلاقيات الطب. Abstract This study of the life of doctor Mohamed Ali Al Bar and his contributions in integrating the experimental sciences Islamic science; where through the analysis of his books and scientific projects, we can observe his pursuit to link experimental medical sciences in miscellaneous issues with Islamic science and Islamic view of universe. He is an exemplary model doctor Muslim in which his character did not separates modern medical science from Islamic science, and he makes a religious and spiritual association pitching sample in medical and scientific practices. He is a model for the character of ancient Muslim doctors who followed Muslim philosophers, doctors, writers and scholars at the same time. This appears in his work as his wisdom of the prohibition of pork and alcohol and drugs and his books on public health, He composed books in scientific miracles in the Quran and Sunnah, and he used the theory of evolution and modern science in proving the ability of Allah, and criticizing the current curricula and explicates a call for curriculum reform in medical schools and other colleges. Encyclopaedia is a medical ethics (moral and doctrinal issues in health professions), which he composed with a group of doctors, This encyclopaedia is a reference medical for students and professors and all medical personnel and Islamic science students and others. It is the most important contributions to integrate science and its integration as a reference for scholars. Keywords: Mohammed Al-Bar, Integrating Science, Criticism, Curriculum, the Encyclopaedia of Medical Ethics.